TELAAH KRITIS ASAL USUL RAJA KECIK DALAM HISTORIOGRAFI TRADISIONAL MELAYU - Atmadinata Atmadinata; Encik Abdul Hajar (Bajang Institute, 2023)
Hikayat Siak and Tuhfat al-Nafis are masterpieces of traditional Malay historiography telling about the pedigree of Raja Kecik, the Sultan of the Johor-Riau Kingdom, from 1718 to 1722. He founded the Kingdom of Siak Sri Indra Pura in 1722, became a sultan there until 1746, and was titled Sultan Abdul Jalil Rahmat Shah. With Regard to the pattern of traditional historiography, Hikayat Siak and Tuhfat al-Nafis are not much different from other traditional historiographies in Nusantara. They were written as instruments of the king's legitimacy for justification from the palace. They are palace centric, contain elements of mythos, and the time of an event was unclear. So far, there are at least two versions of the pedigree of Raja Kecik, as a result of different interpretations among historians who have researched and written about the pedigree of Raja Kecik. Some persist in the narration told in Hikayat Siak and Tuhfat al-Nafis, namely saying he is the son of Sultan Mahmud Shah II, there are also other opinions based on historical sources, like contemporary Dutch documents. Therefore, this paper reveals a critical study based on historical theory and contemporary foreign sources, to prove the narrative of Hikayat Siak and Tuhfat al-Nafis that Raja Kecik was the son of Sultan Mahmud Shah II